2007
DOI: 10.1097/01.cej.0000243858.91642.c9
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin's lymphomas in Alexandria, Egypt; incidence rates and trend study (1995–2004)

Abstract: During the past decades, the incidence of the most common non-Hodgkin's lymphomas has increased dramatically worldwide. In Egypt, it is the fifth most common cancer in both the sexes. The purpose of this study is to study the problem of non-Hodgkin's lymphomas in Alexandria, Egypt: incidence rates and trend. The method employed was record reviewing for estimation of the annual incidence rates of non-Hodgkin's lymphoma and their trends. The general incidence rate of non-Hodgkin's lymphoma was 5.90 in 1995 and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Increases in NHL, particularly among older age groups, have also been observed in Egypt, where the AIDS epidemic is less prominent. The exact causes for this increase are not entirely clear but could be related to altered immune function associated with older age as well as HCV infection, which is prevalent among older Egyptians and has recently been classified by the IARC as having a causal link to NHL 124, 125…”
Section: Resultsmentioning
confidence: 99%
“…Increases in NHL, particularly among older age groups, have also been observed in Egypt, where the AIDS epidemic is less prominent. The exact causes for this increase are not entirely clear but could be related to altered immune function associated with older age as well as HCV infection, which is prevalent among older Egyptians and has recently been classified by the IARC as having a causal link to NHL 124, 125…”
Section: Resultsmentioning
confidence: 99%
“…A review of other published studies from NAF/ME/IN (Castella et al , ; Almasri et al , ; Isikdogan et al , ; Abdel‐Fattah & Yassine, ; Sahni & Desai, ; Akhtar et al , ; Goldman et al , ; Ameen et al , ; Mozaheb et al , ; Yaqo et al , ; Arora et al , ; Otrock et al , ; Mondal et al , ) generally showed relative frequencies of NHL subtypes similar to our study (Table ). The most common lymphoma in all of these studies was DLBCL, ranging from 31% in Egypt (Abdel‐Fattah & Yassine, ) to 59% in the United Arab Emirates (UAE) (Castella et al , ), with most studies reporting a frequency above 40%. The frequency of FL ranged from 1·4% in Iran (Mozaheb et al , ) to 22% in Egypt (Abdel‐Fattah & Yassine, ), with most studies reporting a frequency of less than 15%.…”
Section: Discussionmentioning
confidence: 87%
“…With an HIV prevalence rate of <0·1% in the adult population, Egypt is one of the least affected countries in Africa (http://www.unaids.org/en/regionscountries/countries/). Several studies have reported on the relative frequency of BL in Egypt (Naresh et al , ; Abdel‐Fattah & Yassine, ; Goldman et al , ). One study (Naresh et al , ) reported a high frequency of BL (7%), similar to our findings, whereas the other two studies reported frequencies of only 0·9% (Abdel‐Fattah & Yassine, ) and 0·2% (Goldman et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations